Implementation of The Waterfall Model in Designing a Prescription Abuse Prevention System with Patient Identification in Sleman Regency Pharmacies - Dinasti, Netti Kautsar; Nuryati, Nuryati (Universitas Muhammadiyah Sidoarjo, 2024)
Psychotropic drugs are used to treat psychiatric disorders, but they carry a risk of dependence. Prescription abuse includes using these medications without a prescription and attempting to obtain them illegally. Problems also arise from the improper use of patient cards and doctor's prescriptions. Currently, patient identification is managed separately by each pharmacy, allowing multiple drug purchases at different locations. Based on the preliminary study conducted, there is a need for an integrated recording system between pharmacies to prevent drug misuse, especially psychotropic substances. This requirement aligns with the competencies that must be possessed by medical recorders according to the Decree of the Minister of Health Number 312 of 2020. A medical recorder must be capable of designing health data standards that include data elements, data sets, databases, and the structure and content of health data, ensuring that the data can be used to support healthcare services. This research aims to conduct a needs analysis, design, and assessment for creating a psychotropic patient identification system. The methodology employed in this research follows a waterfall model approach in developing information systems. The stages of the waterfall model include needs analysis, design, implementation, testing, and evaluation. The System Usability Scale (SUS) questionnaire was applied in the testing and evaluation process to assess the level of system usability. The research findings indicate the necessity of an integrated patient identification system among pharmacies to prevent prescription misuse. It is hoped that this system design will serve as a planning model for the next phase. The system usability scale results show that the designed system is effective and acceptable.